2013
DOI: 10.4103/1742-6413.106686
|View full text |Cite
|
Sign up to set email alerts
|

Oncocytic follicular nodules of the thyroid with or without chronic lymphocytic thyroiditis: An institutional experience

Abstract: Background:Oncocytic follicular (OF) cells can be a prominent component of fine needle aspiration (FNA) specimens from neoplasms (adenomas and carcinomas) and nodules arising in multinodular goiter and chronic lymphocytic thyroiditis (CLT). Because OF cells can be present in non-neoplastic and neoplastic thyroid lesions it can be challenging to differentiate between these two in FNA specimens. The aims of this study were to determine the risk of malignancy in cases diagnosed as either oncocytic follicular neop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…A further problem has been underlined in few recent papers by Roh and by Canberk, where the authors compared the different risk of malignancy in cases of oncocytic proliferation with presence or absence of HT, which is often responsible for the pitfalls due to the reactive nuclear atypia and pleomorphisms (22,28). Additionally, our previous paper on HTs stated that the evidence of the lymphocytic component is a key feature of thyroiditis with a 94% histologically benign diagnosis, in the same way that Giorgadze et al expressed their concern in the over-diagnosis of pleomorphisms and grooves in the presence of the lymphocytic component (14,29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A further problem has been underlined in few recent papers by Roh and by Canberk, where the authors compared the different risk of malignancy in cases of oncocytic proliferation with presence or absence of HT, which is often responsible for the pitfalls due to the reactive nuclear atypia and pleomorphisms (22,28). Additionally, our previous paper on HTs stated that the evidence of the lymphocytic component is a key feature of thyroiditis with a 94% histologically benign diagnosis, in the same way that Giorgadze et al expressed their concern in the over-diagnosis of pleomorphisms and grooves in the presence of the lymphocytic component (14,29).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in series described by Nguyen and Gonzales-Campora, the presence of extensive cellularity, large/pleomorphic nuclei, and monomorphic small cells favor a diagnosis of carcinoma, while several other authors have also suggested the evaluation of some further clinical parameters such as gender, size of the lesion, and age (14,15,16,24,25,26,27). In this regard, very few papers have specifically underlined the cytological parameters which might be helpful in discriminating between benign and malignant oncocytic neoplasms, whereas clinical parameters to guide the preoperative decision making have been sought by numerous investigators (9,13,14,22,24,25,26,27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HC carcinoma has been considered a subtype of follicular carcinoma; they show similar clinical behavior [5, 7, 9]. Other studies, however, describe differences in their behavior and oncogene expression [10-12].…”
Section: Discussionmentioning
confidence: 99%
“…15062617). As this was a retcytic follicular adenomas (FAs), and those that exhibit vascular and/or capsular invasion in the absence of diagnostic nuclear features of papillary carcinomas are diagnosed as oncocytic follicular carcinoma [4][5][6][7]. However, the clinical significance of oncocytic change in thyroid tumors remains unclear and controversial.…”
Section: Thyroid Tissuesmentioning
confidence: 99%